The Role of Progressive Web Applications in Enhancing User Engagement: A Systematic Literature Review - Kelvin Vedasto Katto (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2026)
This study aims to explore the role of Progressive Web Applications (PWAs) in enhancing user engagement within the digital ecosystem. PWAs utilize features of both web and native applications to provide capabilities such as offline functionality, push notifications, responsive design, performance optimization, and seamless installation. In this study, the Systematic Literature Review (SLR) methodology was used to analyze 21 peer-reviewed articles obtained from four reputable databases. Findings reveal that PWAs improve user engagement by reducing load times, supporting low-connectivity environments, and enabling real-time communication through push notifications. Furthermore, PWAs reduce development costs by utilizing a single codebase across multiple platforms. However, despite the benefits provided by PWAs, they still encounter various challenges, which include platform-specific limitations (especially on iOS), reduced discoverability compared to native apps, and limited access to advanced device Application Programming Interfaces (APIs). Despite these drawbacks, PWAs represent a promising direction for businesses seeking to deliver efficient, accessible, and engaging digital experiences. This review contributes valuable insights into the future of PWA adoption and its implications for web development